The compliance costs of large corporate taxpayers in Indonesia - Susila, Budi (Curtin University, 2014)
This thesis discusses the results of the first research undertaken to investigate the tax compliance costs of large corporate taxpayers in Indonesia. Using mail survey, the research shows that the costs are significant (i.e. IDR420 million per company per year or AUD38,621 with 2013 exchange rate; the net national compliance costs account for 0.1 per cent of the Gross Domestic Product) and that they are regressive. Staff’s salary contributes almost half of the costs.